Crystal structures of highly specific phosphinic tripeptide enantiomers in complex with the angiotensin‐I converting enzyme. (24th December 2013) - Masuyer, Geoffrey; Akif, Mohd; Czarny, Bertrand; Beau, Fabrice; Schwager, Sylva L. U.; Sturrock, Edward D.; Isaac, R. Elwyn; Dive, Vincent; Acharya, K. Ravi
<x xml:space="preserve">Abstract</x> Human somatic angiotensin‐I converting enzyme (ACE) is a zinc‐dependent dipeptidyl carboxypeptidase and a central component of the renin angiotensin aldosterone system (RAAS). Its involvement in the modulation of physiological actions of peptide hormones has positioned ACE as an important therapeutic target for the treatment of hypertension and cardiovascular disorders. Here, we report the crystal structures of the two catalytic domains of human ACE (N‐ and C‐) in complex with FI, the S enantiomer of the phosphinic ACE/ECE‐1 (endothelin converting enzyme) dual inhibitor FII, to a resolution of 1.91 and 1.85 Å, respectively. In addition, we have determined the structure of AnCE (an ACE homologue from Drosophila melanogaster) in complex with both isomers. The inhibitor FI (S configuration) can adapt to the active site of ACE catalytic domains and shows key differences in its binding mechanism mostly through the reorientation of the isoxazole phenyl side group at the P1′ position compared with FII (R configuration). Differences in binding are also observed between FI and FII in complex with AnCE. Thus, the new structures of the ACE–inhibitor complexes presented here provide useful information for further exploration of ACE inhibitor pharmacophores involving phosphinic peptides and illustrate the role of chirality in enhancing drug specificity. Database Structural data are available in the Protein Data Bank databases under accession numbers 4ca5, 4ca6, 4ca7, 4ca8.